2014
DOI: 10.1007/s00270-014-1013-z
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Fiducial Marker Placement for Image-guided Proton Therapy for Malignant Liver Tumors

Abstract: Transarterial fiducial marker placement appears to be a useful and safe procedure for proton therapy for malignant liver tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Ohta et al [ 14 ] previously reported that the transarterial placement of a fiducial marker resulted in a low complications rate (2%) and a high technical success rate (100%). However, complications such as femoral pseudoaneurysms have also been reported to occur after angiography [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ohta et al [ 14 ] previously reported that the transarterial placement of a fiducial marker resulted in a low complications rate (2%) and a high technical success rate (100%). However, complications such as femoral pseudoaneurysms have also been reported to occur after angiography [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of the HTM would be similar to those of solid fiducial markers used in PT treatment planning of ocular (Newhauser et al 2007), liver (Ohta et al 2015) and prostate cancers (Huang et al 2011, Giebeler et al 2009, which are already clinically employed and are already being studied in the context of in-vivo proton RV (Cho et al 2016). The effect of artifacts on planning CT images and dose shadowing from beam perturbations, which can lead to changes to the planned dose, are already being investigated for various fiducial markers (Huang et al 2011, Cheung et al 2010, Giebeler et al 2009, Newhauser et al 2007, Habermehl et al 2013, Saini et al 2017, and will need to be carefully evaluated for each HTM.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…As a surrogate marker for hepatic tumors, the fiducial marker is required to be implanted as close as possible to the tumor [9]. There have been several reports regarding the transarterial hepatic implantation of an embolization coil [10] and percutaneous transhepatic implantation of a gold marker [11][12][13][14][15][16][17]. The former is more time-consuming, while the latter is technically simpler and more often used.…”
Section: Introductionmentioning
confidence: 99%
“…The former is more time-consuming, while the latter is technically simpler and more often used. In both techniques, non-spherical markers with a size of approximately 1 × 3 mm have generally been used [10][11][12][13][14][15][16][17]. In contrast, true-spherical markers with 2.0-mm diameters 7 are used for automatic precise calculation of the gravity center of the marker in RAR for hepatic malignant tumors [18,19].…”
Section: Introductionmentioning
confidence: 99%